2022
DOI: 10.1097/fjc.0000000000001257
|View full text |Cite
|
Sign up to set email alerts
|

CFTR Suppresses Neointimal Formation Through Attenuating Proliferation and Migration of Aortic Smooth Muscle Cells

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Liang et al, unlike Zhao and Lu, chose the erythrocytes as the research object [9]. They found that CF patients' (whose CFTR is abnormal) erythrocytes couldn't stimulate isolated rabbit lungs to produce endogenous NO while normal erythrocytes had the opposite result.…”
Section: Hypertension and Cftr Genementioning
confidence: 99%
“…Liang et al, unlike Zhao and Lu, chose the erythrocytes as the research object [9]. They found that CF patients' (whose CFTR is abnormal) erythrocytes couldn't stimulate isolated rabbit lungs to produce endogenous NO while normal erythrocytes had the opposite result.…”
Section: Hypertension and Cftr Genementioning
confidence: 99%